Penyederhanaan birokrasi di Kebun Raya Purwodadi BRIN - Dea Marista; Lailul Mursyidah; Fitria Rizki Wijaya (Publisia: Jurnal Ilmu Administrasi Publik, 2022)
This study aims to analyze the simplification of the bureaucracy in the Purwodadi Botanical Gardens, National Research and Innovation Agency (BRIN). This study uses a qualitative approach. Data collection techniques were carried out by reviewing legislation, interviews, and observations. The data analysis technique used by the author in this research is interactive model analysis. Bureaucratic simplification is a mandate from the Regulation of the Minister for Empowerment of State Apparatus and Bureaucratic Reform of the Republic of Indonesia Number 25 of 2021 concerning Simplification of Organizational Structure in Government Agencies for Bureaucratic Simplification. Simplification of the bureaucracy aims to realize effective and efficient government governance by optimizing the use of an electronic-based government system. The implementation of bureaucratic simplification presents its problems and challenges, especially related to employee adaptation.